Nuclear RNA Exosome at 3.1 Å Reveals Substrate Specificities, RNA Paths, and Allosteric Inhibition of Rrp44/Dis3 - Zinder, John C. (Mol Cell, 2016)
The eukaryotic RNA exosome is an essential and conserved 3’ to 5’ exoribonuclease complex that degrades or processes nearly every class of cellular RNA. The nuclear RNA exosome includes a nine-subunit non-catalytic core that binds Rrp44 (Dis3) and Rrp6 subunits to modulate their processive and distributive 3’ to 5’ exoribonuclease activities, respectively. Here, we utilize an engineered RNA with two 3’ ends to obtain a crystal structure of an eleven-subunit nuclear exosome bound to RNA at 3.1 Å. The structure reveals an extended RNA path to Rrp6 that penetrates into the non-catalytic core, contacts between the non-catalytic core and Rrp44 that inhibit exoribonuclease activity, and features of the Rrp44 exoribonuclease site that support its ability to degrade 3’ phosphate RNA substrates. Using reconstituted exosome complexes, we show that 3’ phosphate RNA is not a substrate for Rrp6, but is readily degraded by Rrp44 in the nuclear exosome.